The Effect of Market Value Added, Market Capitalization, and Foreign Ownership on Stock Return in Energy Sector Companies Indonesia Stock Exchange - SUGIANTARA, I Dewa M; ALEXANDER, Stanly W.; WOKAS, Heince R. N. (Journal of Governance, Taxation and Auditing, 2023)
The rate of return is one of the primary considerations in making investment decisions. Stock return is the result obtained from stock investment activities, which can be in the form of realized returns and expected returns. This study aims to determine the effect of Market Value Added, Market Capitalization, and Foreign Ownership on Stock Returns. The object research was carried out at Energy Sector Companies listed on the Indonesia Stock Exchange from 2017 to 2021. This type of research is quantitative research using a purposive sampling technique. There are 26 sample companies selected from 39 companies. The sample is determined based on: 1) Energy sector companies listed on the main board of the Indonesia Stock Exchange for the 2016-2017 period. 2) Energy sector companies that do not publish annual reports for the 2017-2021. 3) Energy sector companies must provide complete data according to the research variables. This study analyzed data using multiple linear regression, with statistical processing using IBM SPSS 26. The analysis of this study shows that market value added and capitalization affect stock returns. Meanwhile, foreign ownership does not affect stock returns.